Sactipeptide Engineering by Probing the Substrate Tolerance of a Thioether‐Bond‐Forming Sactisynthase. Issue 45 (12th October 2022) - Ali, Ataurehman; Happel, Dominic; Habermann, Jan; Schoenfeld, Katrin; Macarrón Palacios, Arturo; Bitsch, Sebastian; Englert, Simon; Schneider, Hendrik; Avrutina, Olga; Fabritz, Sebastian; Kolmar, Harald
Abstract: Sactipeptides are ribosomally synthesized peptides containing a unique sulfur to α ‐carbon crosslink. Catalyzed by sactisynthases, this thioether pattern endows sactipeptides with enhanced structural, thermal, and proteolytic stability, which makes them attractive scaffolds for the development of novel biotherapeutics. Herein, we report the in‐depth study on the substrate tolerance of the sactisynthase AlbA to catalyze the formation of thioether bridges in sactipeptides. We identified a possible modification site within the sactipeptide subtilosin A allowing for peptide engineering without compromising formation of thioether bridges. A panel of natural and hybrid sactipeptides was produced to study the AlbA‐mediated formation of thioether bridges, which were identified mass‐spectrometrically. In a proof‐of‐principle study, we re‐engineered subtilosin A to a thioether‐bridged, specific streptavidin targeting peptide, opening the door for the functional engineering of sactipeptides. Abstract : Sactipeptides are a class of microbial peptides possessing thioether crosslinks. We demonstrate sactipeptide engineering without compromising their post‐translational modification introduced by sactisynthases. A variety of natural and hybrid sactipeptide constructs were generated and analyzed for the presence of thioether crosslinks, demonstrating the possibility to design variants with novel functionalities.